2019
DOI: 10.1029/2019gl082379
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Zonal Mode: An Emerging Source of Indian Summer Monsoon Variability in a Warming World

Abstract: Atlantic Zonal Mode (AZM) and Indian summer monsoon rainfall (ISMR) are known to have an inverse relationship, which means that the cold (warm) phases of AZM result in strong (weak) ISMR. Here, we report that the inverse relationship between AZM and ISMR has significantly strengthened in recent decades. The cause of this strengthening relationship has been investigated. We find a robust increase in interannual variability of sea surface temperature over the eastern tropical Atlantic Ocean in recent decades, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 39 publications
5
47
0
Order By: Relevance
“…The dipole mode (EOF2) explains about 15 % of the total variance, which is associated with the IOD. Our results for the Indian Ocean EOF patterns and their respective contribution to the total variance are consistent with the study by Saji et al (1999). Similarly, the PCs associated with the first EOF over the Pacific Ocean are highly correlated against the observed Niño 3.4 index, with a correlation value greater than 0.8 for both datasets, indicating that EOF1 captures the ENSO-like variability.…”
Section: Observation and Reanalysis Datasupporting
confidence: 90%
See 2 more Smart Citations
“…The dipole mode (EOF2) explains about 15 % of the total variance, which is associated with the IOD. Our results for the Indian Ocean EOF patterns and their respective contribution to the total variance are consistent with the study by Saji et al (1999). Similarly, the PCs associated with the first EOF over the Pacific Ocean are highly correlated against the observed Niño 3.4 index, with a correlation value greater than 0.8 for both datasets, indicating that EOF1 captures the ENSO-like variability.…”
Section: Observation and Reanalysis Datasupporting
confidence: 90%
“…In the observations and reanalysis datasets, empirical orthogonal function (EOF) analysis of the detrended SST anomalies is performed over the tropical Indian Ocean From the two SST datasets, it is observed that both ENSOand IOD-like structures are captured with the second EOF and the first EOF patterns, i.e., a zonal dipole-like structure in the Indian Ocean and the Pacific Ocean, respectively. We use EOF analysis as opposed to standard indices such as the dipole mode index, known as DMI (Saji et al, 1999), and Niño 3.4 to allow each model to exhibit its own patterns as opposed to an imposed structure (Saji et al, 2006;Cai et al, 2009a,b;Liu et al, 2011).…”
Section: Observation and Reanalysis Datamentioning
confidence: 99%
See 1 more Smart Citation
“…One cannot neglect other potential factors for observed rainfall changes during post-1980 La Niña, such as the role of Pacific decadal oscillation (Krishnamurthy & Krishnamurthy, 2014), Atlantic zonal mode (Sabeerali et al, 2019), poleward shift of the jet stream over the north Atlantic (Chang et al, 2001),…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the MISO pattern of year 2010 is similar to that of year 1998 with a weak amplitude. Note that the winter of both year 1998 and year 2010 corresponds to a strong positive phase of the Atlantic Zonal Mode (AZM) [ 36 , 37 ]. The results here confirm the negative correlation between the MISO and the AZM as well as the relatively short predictability of the MISO at the positive phase of the AZM.…”
Section: Predicting the Monsoon Intraseasonal Oscillation (Miso)mentioning
confidence: 99%